Experimental analysis of an all-optical packet router - Reis, C. (2014)
In this paper, we address the experimental implementation of an all-optical packet routing scheme, with contention resolution capability, using interconnected semiconductor optical amplifier (SOA)-based Mach-Zehnder interferometer (SOA-MZI) structures. Cross talk stemming from the blocked packets, due to the nonideal switching performed by the SOA-MZIs, is analyzed in every stage of the routing configuration. The routing functions and states performance are evaluated through bit-error ratio measurements and extinction ratio analysis. © 2014 Optical Society of America.